(untitled) (The Voz a Vos Bulletin, 2021)
It is about the impact and reflections of the "III International Colloquium of Theater Schools" -in its digital edition-, organized by the Bachelor of Performing Arts and its research group Didactics of Performing Arts of the Antonio Nariño University, the Dramatic Art program of the Central University, the Bachelor of Performing Arts from the University of Sonora (Mexico), the Performing Arts program of the Francisco José de Caldas District University - ASAB and the Network of Theater Schools - Ret Colombia, was held from 18 to May 20, 2020.